The hobbit : or, There and back again [compact disc, unabridged] - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (Recorded Books, 1991)
Bilbo Baggins, a respectable, well-to-do hobbit, lives comfortably in his hobbit-hole until the day the wandering wizard Gandalf chooses him to take part in an adventure from which he may never return.